Job Satisfaction of Teachers of Orissa University of Agriculture and Technology, Bhubaneswar, Odisha - Debi Kalyan Jayasingh; N. S. Shivalinge Gowda, Amitava Panja,Maitreyee Tripathy (Indian Journal of Extension Education, 2022)
The study was conducted on three campuses of Orissa University of Agriculture and Technology, Bhubaneswar viz. Bhubaneswar, Chiplima, and Bhawanipatna in 2019 to measure the job satisfaction of teachers working in the University. Ninety respondents from these three campuses were selected for the study using a random sampling procedure. Data was collected from the respondents by implementing the personal interview method. Job satisfaction of teachers was measured with the help of a scale with slight modifications. The majority of teachers possessed a medium level of overall job satisfaction while working at the University. The majority of the variables were found to have a significant positive association with the dependent variable. In addition, variables such as level of aspiration, achievement motivation, perceived workload, mass media exposure, job stress, awards and recognition along with awards and recognition were found to show significantly positively contributing to as well as explaining about sixty-three percent variation of the dependent variable.